Use of Mechanical Circulatory Support in Patients Undergoing Percutaneous Coronary Intervention. Issue 13 (29th September 2015) - Sandhu, Amneet; McCoy, Lisa A.; Negi, Smita I.; Hameed, Irfan; Atri, Prashant; Al'Aref, Subhi J.; Curtis, Jeptha; McNulty, Ed; Anderson, H. Vernon; Shroff, Adhir; Menegus, Mark; Swaminathan, Rajesh V.; et al.
<x xml:space="preserve">Abstract</x> Background— Little is known about the contemporary use of intra-aortic balloon pump (IABP) and other mechanical circulatory support (O-MCS) devices in patients undergoing percutaneous coronary intervention (PCI) in the setting of cardiogenic shock. Methods and Results— We identified 76 474 patients who underwent PCI in the setting of cardiogenic shock at one of 1429 National Cardiovascular Data Registry CathPCI participating hospitals from 2009 to 2013. Temporal trends and hospital-level variation in the use of IABP and O-MCS were evaluated. No mechanical circulatory support was used in 41 286 (54%) patients, 29 730 (39%) received IABP only, 2711 (3.5%) received O-MCS only, and 2747 (3.6%) received both IABP and O-MCS. At the start of the study period, 45% of patients undergoing PCI in the setting of cardiogenic shock received an IABP and 6.7% received O-MCS. The proportion of patients receiving IABP declined at an average rate of 0.3% per quarter, whereas the rate of O-MCS use was unchanged over the study period. The predicted probability of IABP use varied significantly by site (hospital median 42%, interquartile range 33% to 51%, range 8% to 85%). The probability of O-MCS use was <5% for half of hospitals and >20% in less than one-tenth of hospitals. Conclusions— In this large national registry, the use of IABP in the setting of PCI for cardiogenic shock decreased over time without a concurrent increase in O-MCS use. The probability of IABP and O-MCS use varied across hospitals, and the use of O-MCS was clustered at a small number of hospitals.